(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The dangerousness of the presence of Aphidoidea Lachninae, particularly of Cinara cuneomaculata (Del Guercio), on larch near apiaries is pointed out. Indeed the honeydew producted from these insects in autumn causes the storing of a quality of honey that granulates so fast that the bees are not able to solubilize it. Consequently they can die of starvation.